Ponovno odkritje dvoma o ikoni - Mavromatidis, Lazaros Elias (Urbani izziv, 2012)
The main objective of this paper is to define, negotiate and debate radical socio-cultural approaches of landscape creation in today's megacities, within a strict capitalist context. For this reason, it investigates both the theoretical and concrete manner of the spatial expression within an imposed contemporary Foucauldian state of disciplines. Therefore, the research methodology simultaneously develops two different hypotheses in order to bridge the gap between the theoretical explorations and concrete dimension of architectural creation. The primary hypothesis is based on the Lacanian dimension of doubt that is considered in this work as the Chomskyan primitive power that gives birth to every idea or concept, having the potential to exasperate the radical imaginary of each society such as it is defined in Castoriadis' writings. The second main hypothesis is based on an analytical exploration of space creation within strict political and economical contexts. For this purpose, a post-Soviet country served as a case study in order to investigate the cultural landscape values in both communist and capitalist regimes. Hence, focusing on Armenia and especially on Yerevan's landscape transformations during the transition from communism to capitalism, this article first departs from the need to employ a deep theoretical analysis of non-economic factors in order to guide capitalist societies through cooperation with the disadvantaged social structure that has no space in today's megacities and, second, details an original landscape creation sketched by a real recent architectural competition that is seen here as a contemporary Foucauldian state of disciplines. The main object of the architectural composition presented in this contribution is to fulfil the competitions' guidelines - having in mind, however, consolidation of the imposed image of global capitalism with local elements in order to form a Foucauldian heterotopia by allowing different socio-cultural identities to debate, contest or doubt the proposed iconic spatial expression. The article offers a new approach regarding the notion of doubt seen here as a positive element of architectural practice by proposing its continuous existence in the conceptual dimension of architecture.
Keywords: Armenija; Erevan; kulturna pokrajina; mesta; urbana sociologija; urbani prostor; urbani razvoj